Surface Modifications of COP-Based Microfluidic Devices for Improved Immobilization of Hydrogel Proteins: Long Term 3D Culture with Contractile Cell Types and Ischemia Model. - González Lana, Sandra; Randelovic, Teodora; Ciriza, Jesús; López-Valdeolivas, María; Monge, Rosa; Sánchez-Somolinos, Carlos; Ochoa, Ignacio (Jornada de Jóvenes Investigadores del I3A, 2022)
Hydrogel confinement is critical in microfluidics to generate gradients, as cell remodelling process boundaries the development of biological models such as ischemia or fibrosis. Here, we test the immobilization efficiency of collagen hydrogels cells embedded to treated COP-based microfluidic devices to preserve 3D structure and avoid gel contraction.